STRATEGIES ON TEACHING READING COMPREHENSION FOR THE JUNIOR HIGH SCHOOL STUDENTS DURING THE COVID-19 PANDEMIC - Maharani Dyah Ayu Setiawati; Budiasih Budiasih (International Journal of Research on English Teaching and Applied Linguistics, 2022)
English teacher applies certain strategies in teaching reading comprehension to achieve the  objective of learning. Covid-19 pandemic has changed the ways of teaching from face to face  to online learning. This study is intended to investigate strategies the teacher used, to know the  problems faced by the teacher in implementing strategies, and to know how the teacher solves  the problems in implementing strategies on teaching reading comprehension during the covid19 pandemic at junior high school. This descriptive qualitative research was conducted at SMP  2 Manyaran, Central Java. The subject is an English teacher. Observation and interview were  applied to collect the data. Miles and Huberman’s interactive model is used to analyze the data.  The results of this research show that the teacher applies five strategies to teach reading  comprehension during the pandemic covid-19 namely, strategy of identifying the purpose in  reading, skimming the text for main ideas, scanning the text for specific information, analyzing  vocabulary, and implementing L-R-D (Listen-Read-Discuss) strategy. The teacher encounters  several problems in implementing the strategies because the students fail to identify the purpose  of the text, face difficulty to skim the text and analyzing vocabulary. To overcome the problems,  the teacher makes several efforts such as giving more exercises and texts and conducting  discussions. The online learning during the covid-19 pandemic challenges the English teacher  to navigate the students to find the sources of learning using the technologies.